Therapeutic potential of tucidinostat, a subtype-selective HDAC inhibitor, in cancer treatment - Sun, Yichen; Hong, Jing Han; Ning, Zhiqiang; Pan, Desi; Fu, Xin; Lu, Xianping; Tan, Jing (Frontiers in Pharmacology, 2022)
Histone deacetylase (HDAC) is one of the most characterized epigenetic modifiers, modulating chromatin structure and gene expression, which plays an important role in cell cycle, differentiation and apoptosis. Dysregulation of HDAC promotes cancer progression, thus inhibitors targeting HDACs have evidently shown therapeutic efficacy in multiple cancers. Tucidinostat (formerly known as chidamide), a novel subtype-selective HDAC inhibitor, inhibits Class I HDAC1, HDAC2, HDAC3, as well as Class IIb HDAC10. Tucidinostat is approved in relapsed or refractory peripheral T-cell lymphoma (PTCL), advanced breast cancer and relapsed or refractory adult T-cell leukemia-lymphoma (ATLL). Compared with other HDAC inhibitors, tucidinostat shows notable antitumor activity, remarkable synergistic effect with immunotherapy, and manageable toxicity. Here, we comprehensively summarize recent advances in tucidinostat as both monotherapy and a regimen of combination therapy in both hematological and solid malignancies in clinic. Further studies will endeavor to identify more combination strategies with tucidinostat and to identify specific clinical biomarkers to predict the therapeutic effect.